Robotic implantation of intracerebral electrodes for deep brain stimulation - Faria, Carlos André de Oliveira (2013)
This dissertation objective is to contribute for the development of a robotic system towards neurosurgery assistance in Deep Brain Stimulation (DBS) stereotactic procedures. Being DBS neurosurgery typically a long, physically and cognitively demanding procedure; the introduction of a robotic assistant to hold, manipulate and position instrumentation would improve the medical team working conditions and lead to better surgery outcomes. Upon understanding how could the robot be used and what robotic systems were adequate to the task, we implemented a simulation environment to emulate several industrial robot manipulators and the operating room. It was also developed each robot geometric and differential kinematic equations, and control algorithms specifically oriented for DBS neurosurgery assistance. Taking into account the operating room arrangement, the robot characteristics and task requirements, we selected the most apt industrial robotic manipulator and further elaborated on its placement and orientation to achieve utmost performance.